PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE ROUND ROBIN UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN LARUTAN ELEKTROLIT NONELEKTROLIT DAN REAKSI REDOKS DI KELAS X SMAN 1 SEBERIDA - Santi, Nora; Holiwarni, Betty; Azmi, Johni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Research on the application of cooperative learning model Round Robin has been conducted to improve student learning achievement on the topic elektrolit-nonelektrolit and redoks at class X SMAN 1 Seberida. This research is experimental research with randomized control group pretest-posttest design. The sample took in the 10 Maret – 24 April 2014. The sample consisted of two classes, X3 class as experimental class and X1 class as control class. Experimental class is a class that is used cooperative learning model Round Robin, while the control class was not. Data analysis technique used is the t-test. Based on analysis of data obtained tarithmetic > ttable is 3,43 > 1,67, means that the cooperative learning model Round Robin can improve student achievement on the subject of reaction rate in class X SMAN 1 Seberida where the effect of an increase is 15,96%.Keywords: cooperative learning, round robin, learning achievement, elektrolit- nonelektroli and redoks